The role of nuclear energy in the global energy transition - Anna J. Davis (The Oxford Institute for Energy Studies, 2022)
The continuing increase in global greenhouse gas emissions and the likelihood that targets to limit the temperature increase to 1.5o above the level seen at the start of the industrial revolution will be missed has resulted in a growing focus on the development of all forms of carbon-free energy. Solar and wind power have been the main beneficiaries in the power sector, but it is becoming clear that if climate goals are to be met by 2050 then other forms of low or zero emission electricity generation must be prioritised. This has led to something of a renaissance for the nuclear industry, the development of which has been rather stagnant since the Fukushima disaster in Japan in 2011. This OIES paper explores the key motivations for the development of nuclear energy in the current global energy economy. It considers climate change as a key driver, but also discusses energy security and foreign relationships as other important motivating forces. It also outlines the different drivers for countries exporting nuclear technology and those importing it to generate domestic electricity, and provides important detail on the current reactors under construction, the providers of key technologies and the methodologies which various exporters use to gain a competitive position in the nuclear market place.
Keywords: 330; Electricity; energy security; Energy Transition; foreign relations; Nuclear